Application of lattice boltzmann method for lid driven cavity flow - Munir, F.A.; Azmi, M.I.M; Zin, M.R.M; Salim, M.A.; Sidik, N.A.C (Praise Worthy Prize, 2011)
In this paper, numerical simulations to predict fluid flow inside lid driven square and triangular cavity is carried out. The streamline patterns obtained from the simulations is investigated and studied. Lattice Boltzmann Method is used to predict the flow in lid driven cavities. In order to simulate the flow, derivation of macroscopic hydrodynamics equations from the continuous Boltzmann equation need to be performed. Then, the numerical results of shear-driven flow inside square and triangular cavity are compared with results found in literature review. Present study found that flow streamline patterns are affected by the geometry of the cavity and the Reynolds numbers used.